2007
DOI: 10.1159/000109281
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Growth Factor Helps Protect Retina in Experimental Retinal Detachment

Abstract: Purpose: To investigate the expression of nerve growth factor (NGF) and its receptor TrkA on the retina at different time points after retinal detachment (RD) and the protection effect of NGF in experimental RD. Methods: Sprague-Dawley rats were used as an RD animal model by injection of 0.1% sodium hyaluronate under the neurosensory retina. The expression of endogenous NGF and its receptor TrkA in the rat retina was detected using immunohistochemistry. The NGF (5 µg/eye) or phosphate-buffered saline were inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…Glial-neuronal interactions have been studied in the context of enhanced nociception. Studies performed by several groups have demonstrated that microglia and astrocytes in the spinal cord are essential for the initiation and maintenance of pathological pain [3, 3741]. In addition to glial alterations that occur in the spinal cord and nerves, studies have also observed changes in various brain regions that include thalamic microglial activation after injury to the nociceptive spinal cord [3, 42], astrocytic activation in the cingulate cortex after ligation of the sciatic nerve [43], and activation of the nucleus of the solitary tract after colon inflammation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Glial-neuronal interactions have been studied in the context of enhanced nociception. Studies performed by several groups have demonstrated that microglia and astrocytes in the spinal cord are essential for the initiation and maintenance of pathological pain [3, 3741]. In addition to glial alterations that occur in the spinal cord and nerves, studies have also observed changes in various brain regions that include thalamic microglial activation after injury to the nociceptive spinal cord [3, 42], astrocytic activation in the cingulate cortex after ligation of the sciatic nerve [43], and activation of the nucleus of the solitary tract after colon inflammation [44].…”
Section: Discussionmentioning
confidence: 99%
“…The protective function of NGF intraocular administration has been clearly demonstrated in experimental models of ischemic, traumatic, hypertensive injury, 42,43,59 and NGF was recently reported to exert neuroprotective effects by inhibiting the apoptosis of RGCs. 60,61 Interestingly, evidence of NGF acting as an angiogenic agent has emerged from preclinical and clinical studies. NGF, alone or in combination with other biologically active molecules, can have an effect on endothelial cells and on angiogenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this increase, observed after 8 days, is further stimulated by hypoperfusion and even more by exogenous NGF. NGF injected intravitrealy has a great capability to diffuse and to reach the optic nerve itself [ 29 ], as also indicated by the brain diffusion of NGF corneal drops [ 30 ]. A single NGF injection induced the regulation of Bax/Bcl-2 gene expression balance and also the expression of the IEG c-jun in the retina at the earlier time studied (8 days after 2VO ligation), and the effect of this single dose of NGF was long lasting, as indicated by preservation of the optic nerve diameter and myelination and by RGC profile counting.…”
Section: Discussionmentioning
confidence: 99%